2011
DOI: 10.1002/bin.330
|View full text |Cite
|
Sign up to set email alerts
|

Social‐learning Programs Facilitate an Increase in Adaptive Behavior in a Forensic Mental Hospital

Abstract: Deficits in adaptive behavior are a major reason why individuals remain hospitalized or return to inpatient settings. During recovery from a serious mental illness, development of adaptive behavior is as important as reduction of 'symptoms'. Social learning programs (SLPs) have been identified as a best practice in inpatient settings. This study examined whether SLPs facilitated significant growth in adaptive behavior from baseline through one, two, three, and four years of intervention. Direct observational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To understand trends in the data, it is necessary to examine the historic context of the present investigation. Prior to the study period, the hospital embarked on a number of educational and training initiatives including social and independent living skills training for psychosocial rehabilitation—the Lieberman model (Liberman et al, 1998)—and a trauma initiative to create a trauma-sensitive treatment environment (Harris & Fallot, 2001) In addition, one unit in the forensic division with the highest utilization of restraint introduced a Social Learning Program, beginning late 2002 and fully implemented by 2005 (Menditto, Baldwin, O’Neal, & Beck, 1991; Newbill, Paul, Menditto, Springer, & Mehta, 2011). The combination of these interventions led to the dramatic decrease in restraint hours seen in the period from 2005 to 2006 and beyond.…”
Section: Innovations and Preliminary Findingsmentioning
confidence: 99%
“…To understand trends in the data, it is necessary to examine the historic context of the present investigation. Prior to the study period, the hospital embarked on a number of educational and training initiatives including social and independent living skills training for psychosocial rehabilitation—the Lieberman model (Liberman et al, 1998)—and a trauma initiative to create a trauma-sensitive treatment environment (Harris & Fallot, 2001) In addition, one unit in the forensic division with the highest utilization of restraint introduced a Social Learning Program, beginning late 2002 and fully implemented by 2005 (Menditto, Baldwin, O’Neal, & Beck, 1991; Newbill, Paul, Menditto, Springer, & Mehta, 2011). The combination of these interventions led to the dramatic decrease in restraint hours seen in the period from 2005 to 2006 and beyond.…”
Section: Innovations and Preliminary Findingsmentioning
confidence: 99%
“…Another study examining the efficacy of teaching clients with signs of polydipsia how to manage fluid consumption through the use of social-learning procedures revealed that five clients demonstrated fewer daily fluctuations in weight and improvements in biomedical markers of polydipsia (Baldwin et al, 1992). A third study found improvements in the functioning of clients in the SLP who were followed for 1, 2, 3, and 4 years, with results revealing that these clients had meaningful and significant gains in their rates of appropriate behavior over time (Newbill et al, 2011). Similarly, another study investigating the combined effects of the SLP and clozapine found improvements in observed rates of appropriate behavior and decreases in inappropriate behavior for two groups of SMI clients prior to the introduction of clozapine for one of the groups (Menditto et al, 1996).…”
mentioning
confidence: 99%
“…Menditto and colleagues (1996) were among the first to utilize an applied behavioral analytic approach in inpatient clinical settings. Among populations of incarcerated men, it has been shown that adaptive behaviors can develop with the use of social learning programs consequently facilitating significant improvement in functioning over 4 years of intervention (Newbill et al, 2011). Unfortunately, the empirical base focused demonstrating the effectiveness of PBS plan in inpatients settings is otherwise limited.…”
mentioning
confidence: 99%